The impact of liquidity risk on bank performance in Malaysia / Muhammad Zainuddin Mohamed Azudin and Nur Zuliekha Khamis - Mohamed Azudin, Muhammad Zainuddin; Khamis, Nur Zuliekha (2014)
The main objective of this study is to investigate the impact of liquidity risk factors on bank performance in Malaysia. The scope of the study covers from six years period which is from 2008 to 2013. The data is derived from Bankscope which consist of 105 local and foreign banking institutions in Malaysia with number of observation totalling 356. This study employs the bank’s performance as dependent variable while, the independent variables are consumer deposits, cash reserves, non-performing loans and bank’s size. The study finds that consumer deposits, cash reserves, non-performing loans and bank’s size are significant on bank’s performance. However, the study finds the liquidity gap is insignificant towards bank’s performance